Equilibrium Locations in A Spatial Model With Sequential Entry in Real Time - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
I describe the entry process in a spatial market over an infinite time horizon. I show that, as long as the strategy space at the location stage is unbounded, the results derived from the single-period Stackelberg model of entry coincide with those obtained in the infinite horizon model. On the contrary, if the strategy space is bounded, then the later the follower enters, the closer to the center of the market the leader locates at the initial date.
Keywords: 330